STIMULATING STUDENTS SPEAKING USING ENGLISH SPEECHES YOUTUBE CHANNEL - Mutiarani Mutiarani; Atikah Rusiana (Universitas Galuh, 2021)
The purpose of this research was finding that using video can give the students stimulations to learn English especially speaking. Reason why the researcher choose this as the new idea for students because there is so many students whi still cant speak English. This research focus to see the students get a motivation after watching the video and can improve their speaking ability. The video can use while teaching in the class, to see did the students is interesting and get motivate from watching the video from English speeches youtube channel. This researcher using quasi experimental with the pre test, treatment, and post test. The sample on this study were 25 of class 8th Junior High School. To calculate the students score the researcher using manual calculation and the mean results for pre test was 65 and for post test is 79. So there is the difference score between pre tets and post tets, it means using English speeches youtube channel can stimulating and improving students speaking skill.